Traditional Media Confluence Model of Science Popularization Reception Analysis of Sasthra Kala Jathas - Dr.Muhammadali Nelliyullathil (COMMUNICATION & JOURNALISM RESEARCH, 2012)
The study explores the nature of the interconnection between alternative sources of science information and the public in a less privileged social milieu, taking Sasthra Kala Jatha, a traditional media confluence model of science popularization employed by Kerala Sasthra Sahitya Parishad, a prominent Indian science popularization organization. Set in an active audience approach based on reception analysis, it pinpoints the inner dynamics of the pattern of the rural peoples’ consumption and evaluation of the model.